Vertical stratification of beetles in tropical rainforests as sampled by light traps in North Queensland, Australia. (6th July 2015) - Stork, Nigel E.; Stone, Marisa; Sam, Legi
Abstract: How arthropods are distributed within the vertical structure of tropical rainforests is of considerable interest to ecologists. Here, we examine how light trapped beetles are distributed in tropical rainforest in North Queensland, Australia. In January and July 2012, traps were suspended 0 m, 10 m, 20 m and 30 m above the ground in five locations with no more than one trap at any single location on any night. Maximum canopy height at the sites was 35 m. A total of 7299 individuals of 492 morphospecies and 66 families were collected. The species abundance‐based coverage estimator predicted a total species richness of 765. Sample completeness decreases with increasing height from the ground suggesting higher strata were less well sampled. Distance‐based redundancy analysis showed species richness was significantly different between 30 m and all other levels but not between other paired strata. In contrast, both species composition and family composition were significantly distinct for all strata pairs except 10 m with 20 m, and 20 m with 30 m, suggesting that the most distinct strata were 0 m and 30 m. The first two axes of ordination and hierarchical clustering accounted for 46.5% and 17.4% of species composition variation corresponding with season and stratum, respectively. Family level analyses gave similar results to those at the species level. We found stratification of different feeding guilds with herbivores comprising a larger percentage of species in higher strata, whereas saprophages were restricted to the lower strata, reflecting the availability of key resources for these guilds. Fewer species or families were found to be indicators of strata, as measured using IndVal, than for Malaise and flight interception traps (FIT). Dytiscidae and Hydraenidae were abundant but had not been collected using Malaise and FIT. Which species or families are indicators of strata depends on sampling method suggesting multiple sampling methods should be used to establish indicators.